Collective Climate Action, Policy Learning and COVID-19: A Comparative Analysis of the Global Governance and Responses - Palmer, Leigh-Ann (Department of Environmental and Geographical Science, 2022)
This thesis investigates the governance of two global challenges in terms of policy learning and collective action. The COVID-19 pandemic and anthropogenic climate change pose critical challenges to human well-being as much as they depend on collective responses to contain them. The comparative analysis of governance structures in climate change and the COVID-19 pandemic shows similarities and differences. A significant difference is the timing and pace of the responses: while international organisations and governments took drastic measures in response to the spread of the coronavirus, global and national responses for climate change have been comparatively slow. However, similarities emerge in the nature of the responses to these two global challenges: individual behavioural change is necessary to manage the challenges, which rarely occur without political guidance and public policy. The thesis combines the concepts of collective action and policy learning in a conceptual framework for the comparative analysis of global governance between the COVID-19 pandemic and climate change. The success of the rapid and large-scale coordinated response to the COVID-19 disease outbreak has indicated that these conceptual notions are required for global governance and that they can be harnessed on a large-scale to address a GPG or commons problem. Therefore, in order to more effectively address the GPG problem of climate change, these conceptual notions of global governance need to be harnessed not only between international organisations and governments but between governments and non-state actors. The shared policy challenges of both crises, therefore, highlight the importance of good policy design and the coordination of actors. The lessons identified can be broadly applied to the global commons problem of climate change and can help policy makers identify where enhanced policy learning and collective action is required. In particular this should be applied to coordinate policy learning and collective action from municipal to global levels and enhance the participation of the global public for long-term climate policy.